Blended Learning Application in the Accounting Education: Life-based Learning Paradigm - Nuris, D M; Nuraini, U; Nagari, P M (KnE Social Sciences, 2018)
The design of the curriculum at the Universitas Negeri Malang is currently based on life-based learning. This study aimed to describe the application of blended learning in accounting education in terms of life-based learning paradigm. This study used case studies approach on the application of blended learning in the Department of Accounting. Data obtained in the form of a description of the application of blended learning in University and Department of Accounting, lecturer, and student perspectives toward blended learning, the learning process, the benefits gained by them, and the lecturer’s teaching documents. This study found that many students become more active because blended learning is more attractive to them. Students can interact with the lecturer and can study accounting offline and online. Students not only able to manage personal finance daily administratively but also can increase their skills in using information and communication technologies, such as how to search for other learning resources and communicate with others online. Life-based learning approach relates lecture materials to real-life problems, so it is expected to fulfill the community needs. The application of blended learning using a life-based learning approach in many of majors or other universities can be examined for further research. Keywords: blended learning, accounting education, life-based learning